2021
DOI: 10.1681/asn.2020081150
|View full text |Cite
|
Sign up to set email alerts
|

Roxadustat for Treating Anemia in Patients with CKD Not on Dialysis: Results from a Randomized Phase 3 Study

Abstract: BackgroundCurrent anemia therapies for patients with non–dialysis-dependent CKD may require injection and medical visits. Roxadustat, an oral hypoxia-inducible factor prolyl hydroxylase inhibitor, stimulates erythropoiesis and improves iron homeostasis.MethodsIn this double-blind phase 3 study, we randomized patients with non–dialysis-dependent CKD stages 3–5 and hemoglobin <10.0 g/dl (1:1) to thrice-weekly 70-mg oral roxadustat or placebo. Doses were titrated throughout the study based on hemoglobin levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
165
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(176 citation statements)
references
References 43 publications
10
165
1
Order By: Relevance
“…Previously, among Japanese NDD CKD patients not receiving ESAs, the Hb response rate from BL to Week 24 was 94.9% in roxadustat-treated patients [ 13 ]. When roxadustat was compared with placebo in Chinese [ 14 ] and European [ 15 , 16 ] NDD CKD patients with anaemia, Hb response occurred in more roxadustat patients (75.0–86.0%), compared with placebo patients (0.0–8.5%). Additionally, roxadustat demonstrated non-inferiority for Hb maintenance rate versus DA in Japanese patients on haemodialysis [ 11 ] and versus epoetin alfa in global studies of DD patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, among Japanese NDD CKD patients not receiving ESAs, the Hb response rate from BL to Week 24 was 94.9% in roxadustat-treated patients [ 13 ]. When roxadustat was compared with placebo in Chinese [ 14 ] and European [ 15 , 16 ] NDD CKD patients with anaemia, Hb response occurred in more roxadustat patients (75.0–86.0%), compared with placebo patients (0.0–8.5%). Additionally, roxadustat demonstrated non-inferiority for Hb maintenance rate versus DA in Japanese patients on haemodialysis [ 11 ] and versus epoetin alfa in global studies of DD patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roxadustat Increased the Level of Hemoglobin in Non-Dialysis-Dependent Chronic Kidney Disease Patients With Elevated C-reactive Protein Levels Inflammation, which causes iron retention, increased hepcidin formation and impaired erythroid progenitor proliferation was believed as a major contributing factor to anemia (Macdougall et al, 2016;Weiss et al, 2019). In order to assess the influence of inflammation on the effect of roxadustat, we extracted Hb changes in subjects with baseline CRP > ULN from six trials (Chen et al, 2019a;Akizawa et al, 2019c;NCT02174731, 2020;Coyne et al, 2021;Fishbane et al, 2021;Provenzano et al, 2021) (four trials for DD-CKD patients, two trials for NDD-CKD patients). The pooled results showed that for patients with baseline CRP upper than ULN, there was a significant rise of Hb level with the use of roxadustat compared with ESAs and placebo (WMD: 0.63; 95% CI: 0.09-1.17; p 0.02; with heterogeneity [p < 0.00001]; Figure 5 and Table 3).…”
Section: Comparison Of Effects On Iron Utilization Parametersmentioning
confidence: 99%
“…In addition, the duration of the studies enrolled in previous meta-analyses was relatively short, with a maximum follow-up of 26 weeks. Recently, the results of five large phase 3 clinical trials Akizawa et al (2020a), Coyne et al (2021), Fishbane et al (2021), Provenzano et al (2021), Shutov et al (2021) of roxadustat were released, so we updated the meta-analysis. Randomized controlled trials that assessed the efficacy (hemoglobin levels and response) and safety (treatment-emergent adverse events) of roxadustat in DD-CKD and NDD-CKD anemia patients comparing with ESAs or placebo were retriedved with an aim to generate a robust conclusion on the effect of and safety of roxadustat.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple trials have demonstrated that inhibition of PHD effectively improve anemia in those patients with less adverse effects (Akizawa et al, 2020a;Akizawa et al, 2020b;Fishbane et al, 2021). There is no clinical research about effect of PHD inhibition on AKI.…”
Section: Downloaded Frommentioning
confidence: 99%